Simulation of Signal Control Optimization for Intersections in Large-scale Transport Network - Dongxiu Ou; Balmer, M.; Axhausen, K.W.; Decun Dong; Lun Zhang (The Sixth International Conference on Fuzzy Systems and Knowledge Discovery : proceedings, Tianjin, China, 14-16 August 2009, 2009)
MATSim-T (Multi-Agent Traffic Simulation Toolkit) is a simulation platform for large-scale agent-based traffic. Each agent plans its day and performs its activities based on that plan. Then it chooses appropriate routes to reach its destinations. The queue based micro-simulation of MATSim-T ignores the conflicts in intersections. To avoid conflicts in intersections, signal control is added into MATSim-T. This paper focuses on analyzing the effect of signal control on MATSim-T. The capacity of the network is adjusted to satisfy the traffic demand through the green time fraction. The performance of average trip durations is tested based on the traffic flow in the street network of Zurich, Switzerland, which is generated by MATSim-T. The simulation results show that the average trip duration will stabilize after signal optimization even the initial green fraction is different.